Graduate Perception-Based Evaluation of the Philippines Senior High School Science, Technology, Engineering, and Mathematics Curriculum Adequacy: Domain Analysis of Core, Specialized and Contextualized Subjects - Joan B Mariano (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This study aimed to determine the level of adequacy of the Senior High School Science,Technology, Engineering, and Mathematics curriculum in the Philippines by evaluating its three curricular domains: core subjects, specialized subjects, and contextualized subjects, based on the perceptions of college students who completed the Science, Technology, Engineering, and Mathematics strand. Methodology: A quantitative research design was employed using a structured survey questionnaire with a 4-point Likert scale, with reliability established through Cronbach’s alpha (α = 0.87). A total of 159 college Science, Technology, Engineering, and Mathematics students in Benguet, Philippines were selected through random sampling. Data were analyzed using weighted mean and standard deviation, while differences among curriculum domains were examined using the Friedman test, with post hoc pairwise comparisons conducted using the Wilcoxon signed-rank test with Bonferroni correction. Interpretation was guided by established curriculum evaluation frameworks. Main Findings: Core subjects were rated as adequate (M = 3.16, SD = 0.44), specialized subjects as highly adequate (M = 3.60, SD = 0.45), and contextualized subjects as adequate (M = 3.18, SD = 0.50). Mathematics and science-related subjects received higher ratings, whereas contextualized and humanities-related subjects showed greater variability in perceived relevance to Science,Technology,Engineering, and Mathematics preparation. The Friedman test revealed a statistically significant difference among the three domains (χ² = 75.77, p < 0.001), with specialized subjects rated significantly higher than both core and contextualized subjects. Novelty/Originality of this study: This study provides a domain-based evaluation of Science,Technology,Engineering, and Mathematics curriculum adequacy by separately examining core, specialized, and contextualized subjects through the perspective of college-level Science, Technology, Engineering, and Mathematics Senior High School graduates. It advances existing knowledge by offering empirical evidence on curriculum alignment and perceived preparedness, helping inform targeted curriculum refinement within the Philippine K–12 Science, Technology, Engineering, and Mathematics framework.